Masa Kerja, Motovasi Kerja dan Hubungannya Dengan Implementasi Patients Safety Pada Masa Pandemi Covid-19 - Daniel Ginting; Nina Fentiana (Lembaga Pengembangan Kinerja Dosen, 2024)
The Covid-19 pandemic forces hospitals to make patient safety a priority in health services because patient safety is closely related to the quality and image of the hospital itself. The aim of this research is to determine the relationship between length of service and work motivation with the implementation of patient safety by nurses during the Covid-19 pandemic at Bhayangkara Tk III Tebing Tinggi Hospital. The research used a cross sectional design. The sampling technique uses total sampling. Data analysis used chi square. The results of the analysis show that the variables of work experience and work motivation have a p-value <0.05, which means there is a relationship with patient safety.